2003
DOI: 10.1089/107632703764664684
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Fibronectin to Alginate Matrix Improves Peripheral Nerve Regeneration in Tissue-Engineered Conduits

Abstract: Schwann cell (SC) transplantation has been proposed to encourage peripheral nerve regeneration, but an optimal SC-carrying matrix would be needed. The aim of this study was to characterize how the addition of fibronectin to alginate would affect the outcome of nerve regeneration promoted by Schwann cells embedded in this matrix. Genetically labeled rat SCs were obtained by lacZ gene transduction. SCs were suspended in alginate hydrogel matrix with/without addition of liquid fibronectin, and their viability and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
119
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(124 citation statements)
references
References 30 publications
4
119
0
1
Order By: Relevance
“…Both cellular additives were equally effective and superior to the control by all measures of recovery. Finally, in agreement with our results, Mosahebi et al (2003) showed that the regeneration distance at 3 weeks was about 2.5 mm using an empty conduit; elongation was significantly inhibited using an alginate gel even when fibronectin was added, but was augmented when Schwann cells were added to the mixture. Interestingly, the rate of regeneration was 1-2 mm per week, but group differences at 2 or 6 weeks postoperative were absent.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Both cellular additives were equally effective and superior to the control by all measures of recovery. Finally, in agreement with our results, Mosahebi et al (2003) showed that the regeneration distance at 3 weeks was about 2.5 mm using an empty conduit; elongation was significantly inhibited using an alginate gel even when fibronectin was added, but was augmented when Schwann cells were added to the mixture. Interestingly, the rate of regeneration was 1-2 mm per week, but group differences at 2 or 6 weeks postoperative were absent.…”
Section: Discussionsupporting
confidence: 92%
“…Other studies have reported negative results on axonal outgrowth with laminin gels (Labrador et al, 1998) or Matrigel (Valentini et al, 1987;Cai et al, 2004). The conventional view is that axons will easily regenerate through a 10-mm interstump gap by 4 weeks postoperative (Williams, 1987;Kim et al, 1994;Lundborg, 2004), but others disagree (Mosahebi et al, 2003). Haastert et al (2006) used Matrigel as a carrier for Schwann cells transfected to produce FGF-2 in silicone chambers over a 15-mm gap.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schwann cells concurrently synthesize and secrete neurotrophic factors and matrix to guide axon growth and provide a favorable microenvironment for nerve innervation. [25][26][27] In this study, increased proliferation in both Schwann cell and sciatic nerve explants by BMP7 overexpression may explain in part the in vivo beneficial effect of BMP7.…”
Section: Discussionmentioning
confidence: 70%
“…Alginate hydrogel provides a sustained and controlled release of neurotrophich factors in vitro and in vivo (Austin, Bower, Kurek, & Muldoon, 1997;Ko, Dixit, Shaw, & Gitnick, 1995) and freeze-dryed alginate supports axonal regeneration across 50-mm gap in the cat sciatic nerve (Suzuki et al, 1999). Moreover, coating of alginate hydrogel with fibronectin, supports SC viability and neuronal regeneration (Mosahebi, Wiberg, & Terenghi, 2003). An ultrapure endotoxin-free low-viscosity alginate with high manuronic content was used for recombinant NRG-1-type II-β3 (human GGF2, CeNes Pharmaceutical USA) delivery in a poly 3-hydroxybutyrate (PHB) polymer conduit to repair 20mm and 40mm gaps in rabbit common peroneal nerve (Mohanna, Young, Wiberg, & Terenghi, 2003).…”
Section: Nrg1 Release By Biomaterialsmentioning
confidence: 99%